Unlocking English Vocabulary Mastery: An Innovative Learning with the Wordwall Platform - Aqzhariady Khartha; Ince Rezky Naing; Happy Cruzia Rini; Muthmainnah Bahri A. Bohang; Novita Pratiwi; Abdullah Gusti Efendy (Universitas Sulawesi Barat, 2025)
This study aimed to improve English vocabulary mastery using the Wordwall platform for Grade VIII students at SMPN 1 Bontomarannu. Conducted as classroom action research, it comprised two learning cycles involving 38 students as participants. Each cycle presented students with a Wordwall-displayed vocabulary list relevant to the studied topic. Students engaged with the Wordwall by pronouncing words and associating them with relevant images or sentences. Data collection methods included observation, field notes, documentation, and evaluation tests at the end of each cycle. Data were analyzed qualitatively using an interactive approach involving data reduction, presentation, and conclusion drawing. The results showed a significant improvement in students’ English vocabulary mastery after implementing the Wordwall platform. This was evident from the vocabulary test results, which showed increased average scores from one cycle to the next. Observations also highlighted students’ active participation and enthusiasm in engaging with the Wordwall. Furthermore, the improvement in vocabulary mastery positively correlated with better learning outcomes. In conclusion, the use of the Wordwall platform effectively enhanced students’ English vocabulary mastery. It visually supported vocabulary development and helped students build stronger associations between words and their contexts. Teachers are encouraged to use the Wordwall platform in English teaching to improve students' vocabulary skills. Keywords: Wordwall Platform, English Vocabulary Mastery, Student Engagement